2019
DOI: 10.26735/16586794.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Measures in the Treatment of Aluminum Phosphide Poisoning as a Trial to Reduce Mortality at Assiut University Hospital, Egypt

Abstract: Aluminum phosphide (AlP) poisoning is a major problem, accounting for many Emergency Unit visits and hospitalization with increasing incidence of AlP toxicity in the last few years. In spite of the progress achieved in the field of toxicology and associated therapies, AlP is still responsible for a high rate of mortality due to the rapid onset of life-threatening symptoms, ineffective treatment and inadequate data on the efficacy of therapeutic interventions. AlP poisoning is a serious medical emergency demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This finding was reinforced by investigations in Morocco and Egypt, which reported a death rate of 49% and 45.5%, respectively. 12,13 However, a study conducted at Felege Hiwot Referral Hospital Bahir Dar and Tehran-Iran found a lower mortality rate of 31.2% and 24.06%, respectively. 4,14 This disparity could be attributed to differences in study period, study population, medication availability, and both studies explain that most of the tablets were exposed to air or expired tablets, which have lower phosphide content due to gradual release of phosphine gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was reinforced by investigations in Morocco and Egypt, which reported a death rate of 49% and 45.5%, respectively. 12,13 However, a study conducted at Felege Hiwot Referral Hospital Bahir Dar and Tehran-Iran found a lower mortality rate of 31.2% and 24.06%, respectively. 4,14 This disparity could be attributed to differences in study period, study population, medication availability, and both studies explain that most of the tablets were exposed to air or expired tablets, which have lower phosphide content due to gradual release of phosphine gas.…”
Section: Discussionmentioning
confidence: 99%
“…This was also the conclusion of an Egyptian study. 13,20 This is because rodenticide poisoning disrupts electrolytes, resulting in cardiac arrhythmia and cardiogenic shock. Hypotension, on the other hand, will cause tachycardia as a compensatory strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Managements of ALP poisoned patients aim to prevent phosphine gas release and to keep people alive by administering proper resuscitation techniques until the phosphine has been eliminated from the body. Hence, early gastric lavage is crucial (Amiri et al, 2016;H. Abdel-Hady et al, 2019).…”
Section: Discussionmentioning
confidence: 99%